LEXICAL-SEMANTIC PROPERTIES OF HEMATOLOGICAL TERMS IN MEDICINE - Ergashova Iroda (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: In the field of Medicine, hematological Terms form an interesting and complex material for studying the lexical-semantic edges of linguistics. Hematology is the  field  of  medicine  that  studies  blood  and  its  composition,  blood  diseases,  their diagnosis and treatment, and the terminology in this area has clear, systematic and specific lexical-semantic properties. Lexical-semantic analysis of hematological terms on the example of English and Uzbek languages shows the integration of language and medical  science,  and  also  allows  you  to  identify  terminological  connections  and differences between the two languages.